The role and status of evidence and innovation in the healthy towns programme in England: a qualitative stakeholder interview study. Issue 1 (21st September 2012) - Goodwin, Denise May; Cummins, Steven; Sautkina, Elena; Ogilvie, David; Petticrew, Mark; Jones, Andy; Wheeler, Katy; White, Martin
Abstract : Background: In 2008, the Healthy Community Challenge Fund commissioned nine 'healthy towns' in England to implement and evaluate community-based environmental interventions to prevent obesity. This paper examines the role of evidence in informing intervention development, innovation and the potential for programmes to contribute to the evidence base on the effectiveness of interventions that tackle population obesity. Method: Twenty qualitative interviews with local programme stakeholders and national policy actors were conducted. Interview transcripts were coded and thematically analysed. Initial analyses were guided by research questions regarding the nature and role of evidence in the development and implementation of the healthy towns programme and the capacity for evidence generation to inform future intervention design, policy and practice. Findings: Stakeholders relied on local anecdotal and observational evidence to guide programme development. While the programme was considered an opportunity to trial new and innovative approaches, the requirement to predict likely health impacts and adopt evidence-based practice was viewed contradictory to this aim. Stakeholders believed there were missed opportunities to add to the existing empirical evidence base due to a lack of clarity and planning, particularly around timing, in local and national evaluations. Conclusions: A strong emphasis on relying on existing evidence-based practice and producing positive impacts and outcomes may have impeded the opportunity to implement truly innovative programmes because of fear of failure. Building more time for development, implementation and evaluation into future initiatives would maximise the use and generation of robust and relevant evidence for public health policy and practice.